2024
DOI: 10.1242/bio.060278
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model of mitochondrial disease phenotypic heterogeneity

Lucy Granat,
Debbra Y. Knorr,
Daniel C. Ranson
et al.

Abstract: Mutations in genes that affect mitochondrial function cause primary mitochondrial diseases. Mitochondrial diseases are highly heterogeneous and even patients with the same mitochondrial disease can exhibit broad phenotypic heterogeneity, which is poorly understood. Mutations in subunits of mitochondrial respiratory complex I cause complex I deficiency, which can result in severe neurological symptoms and death in infancy. However, some complex I deficiency patients present with much milder symptoms. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This manipulation did not promote the persistence of medulla NBs at 24 hr APF ( Figure 1—figure supplement 1L–N ), suggesting that med12 is likely important in the NE but not the NBs. Next, we knocked down ND75, a component of the Complex I of the electron transport chain by RNAi ( Granat et al, 2024 ) to test the requirement of OxPhos for medulla NB termination. Our data showed that no persistent NBs were found in ND75 RNAi clones at 24 hr APF ( Figure 1—figure supplement 1A, D, E ).…”
Section: Resultsmentioning
confidence: 99%
“…This manipulation did not promote the persistence of medulla NBs at 24 hr APF ( Figure 1—figure supplement 1L–N ), suggesting that med12 is likely important in the NE but not the NBs. Next, we knocked down ND75, a component of the Complex I of the electron transport chain by RNAi ( Granat et al, 2024 ) to test the requirement of OxPhos for medulla NB termination. Our data showed that no persistent NBs were found in ND75 RNAi clones at 24 hr APF ( Figure 1—figure supplement 1A, D, E ).…”
Section: Resultsmentioning
confidence: 99%